Incidence of Pathogenic Variants in Those With a Family History of Pancreatic Cancer - Macklin, Sarah K.; Kasi, Pashtoon M.; Jackson, Jessica L.; Hines, Stephanie L. (Frontiers in Oncology, 2018)
Discovery of a hereditary cancer syndrome can be one of the factors that determine whether a healthy individual completes pancreas cancer screening or whether an individual with cancer receives certain chemotherapies. Retrospective review was completed to determine the likelihood of detection of a pathogenic variant causing a hereditary cancer syndrome based on personal and family history. Study was completed through the hereditary cancer clinic at Mayo Clinic Florida over a 6 year period, 1/2012 through 1/2018. All participants were referred based on suspicion for a hereditary cancer syndrome based on personal and/ or family history. Patients’ personal oncologic history at time of consultation was recorded, as well as, cancer diagnoses in the family history and the number of family members with a history of pancreas cancer. Test result and gene name, if variant was pathogenic or likely pathogenic, were noted as well. A total of 2019 patients completed genetic testing during study period. Personal history of cancer included a variety of primaries, including breast (N=986), ovarian (N=119), colon (N=106), prostate (N=65), and pancreas (N=59). A positive result was discovered in 11% of the total group. Two hundred and eighty five reported a family history of pancreas cancer. The incidence of pathogenic variants was 13% (37/285) in those with any family history and 23% (13/56) in those with two or more relatives with pancreatic cancer. Those with multiple relatives with pancreatic cancer were significantly more likely to carry a pathogenic variant than those with a personal history of breast cancer under the age of 45 (23.2% vs. 11.9%, p=0.02). Presence of multiple family members with a reported history of pancreatic cancer significantly increased the likelihood that a pathogenic variant would be identified in the patient even over other significant risk factors, like personal history of early onset breast cancer.